Microalgae role in sustainable bioenergy generation as determined by light microscopy. Issue 5 (3rd January 2022) - Abbas, Moneeza; Shaheen, Shabnum; Pervaiz, Mahnoor; Jaffer, Mehwish; Tahir, Arfa
Abstract: The main aim of this study was to explore the role of light microscopy in the identification of microalgae as a source of study. Three microalgal species (Nostoc, Anabaena, and Volvox) were identified by light. In this study, different parameters of the oil extraction process from algae biomass were studied. The samples of Nostoc, Anabaena, and Volvox were collected from the freshwater bodies in Lahore, and the samples were identified by light microscopy. Pretreatment of algae was done which includes harvesting, drying, and grinding. The sun drying of sample was done. Solvent extraction was done for the extraction of oil from algal cells. Solvent n‐hexane and diethyl ether were used alone as well as in combination. Effects of n‐hexane to oil ratio, size of algal biomass, and contact time on the percentage yield of extracted oil were studied and analyzed. It was concluded that maximum amount of oil was extracted from algae by using a greater ratio of solvent to algal biomass, maximum contact time, and smaller algal biomass size. The extracted oil yield was satisfactory, demonstrating the potential of microalgae for biodiesel production. It was discovered that if algal oil is subjected to transesterification, it can be turned into biodiesel, and light microscopy can be used to assess anatomical characteristics. However, more research will be required for transesterification. Abstract : The research was planned to determine the utilization of light microscopically for identifying three different microalgae. Then by culturing, the production of biodiesels from collected sources was done. Result outcomes indicated that microalgae become the source of biodiesel production.